Synthesis and Characterization of Micro and Nano Ba3-xKxHx(PO4)2 and Ba3-xNaxHx(PO4)2. Issue 1611 (30th July 2014) - Bang, Sun Hwi; Chun, Sam; Highower, Adrian
ABSTRACT: Ba3-x Kx Hx (PO4 )2 is a candidate solid-state proton conductor for solid acid fuel cells that is water-insoluble. The measured conductivity of ∼ 2.4 10 -5 S cm -1 for the composition x=0.80 at 250°C is not competitive for solid acid fuel cell applications. This work investigates a methods for synthesizing solid acid electrolytes with the strategy of increasing proton conductivity by cation substitution and decreasing particle size. We report on the synthesis of nano Ba3-x Kx Hx (PO4 )2 to a novel Ba3-x Nax Hx (PO4 )2 . X-ray diffraction was used to confirm the Ba3 (PO4 )2 crystal structure and measure lattice strain as a function of cation substitution. SEM confirmed the morphology of micro Ba3-x Nax Hx (PO4 )2 is substantially different from micro Ba3-x Kx Hx (PO4 )2, suggesting that Ba3-x Nax Hx (PO4 )2 has a different growth kinetics.